Karakteristik Penyakit Mahasiswa – Mahasiswi Peserta Pesantren di Klinik Pesantren Mahasiswa Darul Mukhlisin UMI Padanglampe Tahun 2023 - Mappaware, Nasrudin Andi; Syamsu, Rachmat Faisal; Royani, Ida; Mokhtar, Shulhana; Makmun, Armanto; Shamad, Muhammad Ishaq; Bazith, Akhmad; Thahir, Ilyas; Mayo, Abbas Ali; Abdillah, Andi Rachmat (Innovative: Journal Of Social Science Research, 2025)
This study aims to identify the characteristics of the most common diseases that occur at the Darul Mukhlisin UMI Padanglampe Student Islamic Boarding School Clinic in 2023. The method used is a descriptive observational research design with a retrospective cohort study approach, where secondary data from patient medical records were collected and analyzed. The results showed that the most common diseases found were Acute Respiratory Tract Infections (ARI), common cold, dyspepsia, hypertension, and gingivitis. Infectious diseases such as ARI and common cold dominate, while non-communicable diseases, including dyspepsia, hypertension, and gingivitis, also have a significant prevalence. Environmental and lifestyle factors play an important role in the high incidence of these diseases. Therefore, improving sanitation, health education, and routine health checks are needed to reduce the prevalence of the disease. Further research is needed to explore the relationship between risk factors and disease incidence and to evaluate the effectiveness of health intervention programs in the Islamic boarding school environment.